The Relationship between Uric Acid and the Development, Complication, and Prognosis of Atrial Fibrillation: The Views from a Clinical Study - Jian Yang; Lian Lou; Xuan Zhang; Yuxiao Chen; Weier Zhou; Chi Zhang; Xiaogang Guo; Shenjiang Hu (International Journal of Endocrinology)
A large number of studies suggest that uric acid (UA) is related to the occurrence, complications, and prognosis of atrial fibrillation (AF). However, the guidelines did not clearly elaborate on this issue. The current research results need to be summarized to analyze the association between UA and AF. This study found that in the current clinical research on the relationship between UA and AF, studies mainly focus on the development or complications of AF. A lot of repetitive work does not deepen awareness of this question. In contrast, studies investigating the effects of UA-lowering therapy on the management of AF are limited. The only reports deny the protective effect of UA-lowering therapy. For now, we suggest that UA is close to the occurrence and progression of AF; therefore, it may have important significance as a clinical marker. The role of UA-lowering therapy in the management of AF is one of the next key issues to be explored. It will be a meaningful topic to focus on the latest research on AF ablation and to conduct a secondary analysis to explore the prognostic impact of UA on the latest treatment methods for AF. Multiomics techniques may allow us to have a deeper understanding of the role of UA in AF management in the future.